Editor's Choice – Open Thoracic and Thoraco-abdominal Aortic Repair After Prior Endovascular Therapy. (July 2018) - Keschenau, Paula R.; Ketting, Shirley; Mees, Barend; Barbati, Mohammad E.; Grommes, Jochen; Gombert, Alexander; Schurink, Geert Willem H.; Kotelis, Drosos; Jacobs, Michael J.
Abstract : Objective: The aim was to present current results of open thoracic and thoraco-abdominal aortic repair as secondary procedure after prior endovascular therapy. Methods: This was a retrospective cross border single centre study. From 2006 to July 2017 45 open thoracic aortic (TAA) or thoraco-abdominal aortic aneurysm (TAAA) operations were performed on 44 patients (median age 58 [15–80] years) as secondary surgery after previous endovascular therapy comprising TEVAR ( n  = 38; 86%), EVAR ( n  = 3; 7%), fenestrated EVAR ( n  = 1; 2%) and TEVAR plus EVAR ( n  = 1; 2%). Eleven patients (25%) had had previous open aortic surgery at the secondary surgery site. Indications for TAA(A) repair were Type I endoleak ( n  = 10; 23%), post-dissection aneurysm progression due to persisting false lumen perfusion ( n  = 8; 18%), proximal/distal disease progression ( n  = 16; 36%), device fracture/dislocation ( n  = 4; 9%), infection ( n  = 5; 11%), and initial endograft misplacement ( n  = 1; 2%). The operations included descending thoracic aortic repair ( n  = 13, 29%), TAAA Type I ( n  = 4; 9%), Type II ( n  = 5; 11%), Type III ( n  = 13; 29%), Type IV ( n  = 7; 16%), and Type V repair ( n  = 3; 7%) with simultaneous arch repair in 18% ( n  = 8). The median time to secondary surgery was 36 (2–168) months. The median follow up was 39 (3–118) months. Results: In hospital mortality was 20% ( n  = 9) due to intra-operative aneurysm rupture, pneumonia induced sepsis, hemorrhagic cerebellar infarction, mesenteric ischaemia, broncho-esophageal fistula, and multiorgan failure (1/9) as well as haemorrhage (3/9). Estimated survival was 73% at 1 year and 71% overall. The most frequent complications were pneumonia ( n  = 19; 43%), bleeding requiring revision ( n  = 11; 25%) and sepsis ( n  = 14; 32%). Transient dialysis was required in 32% ( n  = 14), permanent dialysis in 6% ( n  = 2). Permanent spinal cord deficit (paraparesis) occurred in 6% ( n  = 2). Estimated freedom from aortic re-intervention was 86%. Conclusion: Open TAA(A) repair as a secondary procedure after previous endovascular aortic therapy is an important treatment option even in the endovascular era. It represents a durable treatment that can produce respectable outcomes. Yet the peri-operative morbidity and mortality are relevant and a specialised team and infrastructure are mandatory for these complex procedures. Therefore, centralisation is required.